Kritik dan Relevansi Paradigma Komunikasi Pembangunan di Era Digital: Studi Kasus pada UMKM Batik di Kota Pekalongan - Yusup, Muhammad; Hasibuan, Muhammad Yusup (Jurnal Dakwah dan Masyarakat, 2025)
This study aims to critique and assess the relevance of the classical development communication paradigm in the context of the digital era, characterized by decentralized information flows and increasingly broad public participation. Although development communication was initially oriented towards a linear, top-down, and modernization approach, social dynamics in the digital era demand a more dialogic, collaborative communication model that utilizes technology. To deepen the analysis, this study uses a case study of the Batik UMKM empowerment program in Pekalongan City, which since 2019 has utilized social media, digital marketing platforms, and community information systems as a means of developing the community's creative economy. Using qualitative methods using literature review and document analysis techniques, this study found that the classical development communication paradigm is no longer adequate to address the complexity of digital social change. Successful communication patterns instead emerge from participatory models based on digital networks, strengthening social capital, and collaboration between government, communities, and creative industry actors. This study contributes to the development of development communication theory by offering a critical framework that integrates the concepts of digital participation, co-creation, and community-driven development as a more adaptive approach in the digital era.   Penelitian ini bertujuan mengkritisi sekaligus menilai relevansi paradigma komunikasi pembangunan klasik dalam konteks era digital yang ditandai oleh arus informasi yang desentralistik dan partisipasi publik yang semakin luas. Meskipun komunikasi pembangunan awalnya berorientasi pada pendekatan linear, top–down, dan modernisasi, dinamika sosial di era digital menuntut model komunikasi yang lebih dialogis, kolaboratif, serta memanfaatkan teknologi. Untuk memperdalam analisis, penelitian ini menggunakan studi kasus pada program pemberdayaan UMKM batik di Kota Pekalongan, yang sejak 2019 memanfaatkan media sosial, platform digital marketing, dan sistem informasi komunitas sebagai sarana pengembangan ekonomi kreatif masyarakat. Melalui metode kualitatif dengan teknik kajian Pustaka dan analisis dokumen, penelitian ini menemukan bahwa paradigma komunikasi pembangunan klasik tidak lagi memadai untuk mengatasi kompleksitas perubahan sosial digital. Pola komunikasi yang berhasil justru muncul dari model partisipatif berbasis jejaring digital, penguatan modal sosial, serta kolaborasi antara pemerintah, komunitas, dan pelaku industri kreatif. Penelitian ini berkontribusi pada pengembangan teori komunikasi pembangunan dengan menawarkan kerangka kritis yang mengintegrasikan konsep digital participation, co-creation, dan community-driven development sebagai pendekatan yang lebih adaptif di era digital.